DINAMIKA HASIL MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA BERBASIS GOOD GOVERNANCE TERHADAP PEMBANGUNAN INFRASTRUKTUR DI DESA RANAH SINGKUANG KECAMATAN KAMPAR TAHUN 2023 - Roja, Hefnila Oktavia; Susanto, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
Village development based on the principles of Good Governance emphasizes the importance of participation, transparency, and accountability in the development planning process, particularly through the Village Development Planning Meeting (Musyawarah Perencanaan Pembangunan Desa/Musrenbang) as a strategic forum for capturing community aspirations. Musrenbang is expected to produce infrastructure development plans that are responsive to community needs and aligned with the village’s fiscal capacity. However, in practice, gaps are often found between Musrenbang outcomes and development realization, indicating that the principles of Good Governance have not been optimally implemented in village governance. This study aims to analyze the dynamics of Good Governance-based Musrenbang outcomes on infrastructure development in Ranah Singkuang Village, Kampar District, in 2023. The research employs a qualitative approach using interviews, observations, and documentation as data collection techniques. The findings show that out of more than 30 infrastructure proposals submitted through the 2023 Musrenbang, only three activities were realized in 2024. This condition is influenced by budget constraints, shifts in policy priorities, low community involvement in final decision-making, and weak transparency and accountability within the village government. These findings confirm that Musrenbang in Ranah Singkuang Village remains procedural rather than substantive, highlighting the need to strengthen Good Governance principles, particularly participation, transparency, and accountability. Keywords: Musrenbang, village development, infrastructure, community participation, good governance.